The Influence of Entrepreneurial Orientation and Innovation on the Performance of MSMEs in Indonesia: A Case Study of Generation Z MSMEs - Balya, Muhammad Rafi Raihan; Yuldinawati, Lia (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to investigate the influence of entrepreneurial orientation and innovation on the performance of Micro, Small, and Medium Enterprises (MSMEs) operated by Generation Z in Indonesia. Using a quantitative approach, data were collected through a structured questionnaire distributed to 400 young MSME owners across various regions. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that entrepreneurial orientation significantly and positively affects both innovation and business performance, while innovation also has a significant positive impact on performance. These results highlight the importance of fostering entrepreneurial behavior and innovation capabilities to enhance the competitiveness of Generation Z entrepreneurs. The study offers practical implications for policymakers, educators, and support institutions to strengthen youth-led MSMEs in the digital economy.